Mars impact probability analysis for the Hayabusa-2 NEO sample return mission. Issue 9 (1st May 2016) - Chujo, Toshihiro; Tsuda, Yuichi; Shimizu, Yukio; Yoshikawa, Makoto; Yano, Hajime
Abstract: This paper reports the results of an analysis of the Mars impact probability for the Hayabusa-2 spacecraft to comply with the COSPAR planetary protection requirements. Since Hayabusa-2 is equipped with an ion engine system and its trajectory accommodates the non-ballistic trajectory, effective analysis methods are introduced. The results show that the Mars impact probability is sufficiently low for the Hayabusa-2 mission to fully comply with the COSPAR planetary protection requirements.